Task Shifting and Skin Punch for the Histologic Diagnosis of Kaposi’s Sarcoma in Sub-Saharan Africa: A Public Health Solution to a Public Health Problem - Laker-Oketta, Miriam O.; Wenger, Megan; Semeere, Aggrey; Castelnuovo, Barbara; Kambugu, Andrew; Lukande, Robert; Asirwa, F. Chite; Busakhala, Naftali; Buziba, Nathan; Diero, Lameck; Wools-Kaloustian, Kara; Strother, Robert Matthew; et al. (Oncology, 2015)
Fueled by HIV, sub-Saharan Africa has the highest incidence of Kaposi’s sarcoma (KS) in the world. Despite this, KS diagnosis in the region is based mostly on clinical grounds. Where biopsy is available, it has traditionally been excisional and performed by surgeons, resulting in multiple appointments, follow-up visits for suture removal, and substantial costs. We hypothesized that a simpler approach – skin punch biopsy – would make histologic diagnosis more accessible. To address this, we provided training and equipment for skin punch biopsy of suspected KS to three HIV clinics in East Africa. The procedure consisted of local anesthesia followed by a disposable cylindrical punch blade to obtain specimens. Hemostasis is facilitated by Gelfoam ®. Patients removed the dressing after 4 days. From 2007 to 2013, 2,799 biopsies were performed. Although originally targeted to be used by physicians, biopsies were performed predominantly by nurses (62%), followed by physicians (15%), clinical officers (12%) and technicians (11%). There were no reports of recurrent bleeding or infection. After minimal training and provision of inexpensive equipment (USD 3.06 per biopsy), HIV clinics in East Africa can integrate same-day skin punch biopsy for suspected KS. Task shifting from physician to non-physician greatly increases access. Skin punch biopsy should be part of any HIV clinic’s essential procedures. This example of task shifting may also be applicable to the diagnosis of other cancers (e.g., breast) in resource-limited settings.
Keywords: Kaposi’s sarcoma ·; HIV/AIDS; Skin punch biopsy; Task shifting; Africa